2019
DOI: 10.1002/adma.201805671
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence Anisotropy Reloaded—Emerging Polarization Microscopy Methods for Assessing Chromophores' Organization and Excitation Energy Transfer in Single Molecules, Particles, Films, and Beyond

Abstract: Fluorescence polarization is widely used to assess the orientation/rotation of molecules, and the excitation energy transfer between closely located chromophores. Emerging since the 1990s, single molecule fluorescence spectroscopy and imaging stimulate the application of light polarization for studying molecular organization and energy transfer beyond ensemble averaging. Here, traditional fluorescence polarization and linear dichroism methods used for bulk samples are compared with techniques specially develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 177 publications
1
43
0
Order By: Relevance
“…In π‐conjugated polymers the connection between the electronic properties and the morphology of the chain is prominent . A prime example is PFO, for which its morphology can even be separated into distinct phases (the α‐, β‐, and γ‐phase), where each phase has its own very distinct properties .…”
Section: Figurementioning
confidence: 99%
“…In π‐conjugated polymers the connection between the electronic properties and the morphology of the chain is prominent . A prime example is PFO, for which its morphology can even be separated into distinct phases (the α‐, β‐, and γ‐phase), where each phase has its own very distinct properties .…”
Section: Figurementioning
confidence: 99%
“…Therefore, we selected 50 wt % as the optimal dye loading, exhibiting a QY of 52 %. In addition, increasing the dye loading up to 50 wt % led to an over 100‐fold drop in the fluorescence anisotropy (Figure S10), which suggested strong coupling of closely packed dyes inside NPs and efficient excitation energy migration within donor dyes independently from the acceptor . This process should ensure long‐distance excitation energy transport to the acceptor leading to an overall FRET beyond the Förster radius (Scheme A) …”
Section: Resultsmentioning
confidence: 57%
“…A similar large number of acceptors are also needed to ensure FRET from upconverting NPs (UCNPs) and dye‐doped silica NPs . One way to go beyond the Förster radius is to use light‐harvesting nanomaterials in which the strongly coupled energy donors communicate through excitation energy migration, which allows transporting the energy through long distances up to the FRET acceptor. Previous works showed that energy migration can improve FRET efficiency in both dye‐doped silica NPs and UCNPs .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure S4 (Supporting Information), the apparatus consisted of a linearly polarized semiconductor laser (λ = 405 nm), quarter‐wave plate, sample stage, lens, polarizer, and fiber‐optic spectrometer. The polarization ratio can be calculated according to Equation P=Imax IminImax + Imin…”
Section: Resultsmentioning
confidence: 99%